Black Panther. Vol. 3, All this and the world, too - Ridley, John, 1965- (Marvel Worldwide, Inc., 2023)
"T'Challa has been banished from his homeland! Searching for purpose, the Black Panther returns to the Avengers - just in time for a mysterious group of terrorists to seize control of global communications! And when that organization proves to be eerily connected to Wakanda and T'Challa himself, his standing even among Earth's Mightiest Heroes comes into question - as does everything he has come to know and trust over the course of recent events. The message is clear: If T'Challa isn't ready to be a team player, he doesn't belong on a team. With no kingdom, no Avengers and no allies, who is left to aid T'Challa against this monster of his own making? Would you believe - the Sub-Mariner?! The most bitter rivalry in Marvel Comics reaches a surprising turning point!"--Amazon.